PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PT INDOFARMA TBK PERIODE 2013 - 2022 - Nursanda Putri, Fika; Oktrima, Bulan (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio and Debt to Equity Ratio partially on Return on Assets and to determine the influence of the Current Ratio and Debt to Equity Ratio simultaneously on Return on Assets at PT Indofarma Tbk for the 2013 - 2022 period. This research uses quantitative methods. The analytical method used is calculating the results of each descriptive test variable, classical assumption test, simple and multiple linear regression, coefficient of determination, correlation coefficient, and hypothesis testing. Based on the results of research conducted, the Liquidity Ratio (Current Ratio) variable was partially proven to have no effect on Return on Assets based on the t-test at a=0.05, obtained tcount > ttable (1.559<2.365) with a significant value of 0.163>0.05. The Debt to Equity Ratio variable was partially proven not to influence Return on Assets based on the t-test at a=0.05, obtained tcount > ttable (-9.938<2.365) with a significant value of 0.000<0.05. The variables Current Ratio (X1) and Debt to Equity Ratio (X2) were simultaneously proven to influence Return on Assets (Y) based on the f-test at a=0.05, obtained Fcount > Ftable (76.455>4.74) with a significant value of 0.000< 0.05. The coefficient of determination test results show that the Adjusted R Square value is 0.944, so (KD = r2 x 100% = 0.944 x 100% = 9.0%) so it can be concluded that the Current Ratio (CR) and Debt to Equity Ratio (DER) have an effect of 9.0% of Return on Assets (ROA), while the remaining 91.0% is influenced by other variables not examined in this research.